Evaluación del comportamiento del sistema eléctrico de distribución frente al ingreso de fuentes de energía renovable no convencional. - Aguirre Manosalvas, David Eduardo (2023)
This project evaluates the behavior of an electrical distribution system before the entry of non conventional renewable energies, in order to find an efficient way where renewable generation systems are implemented to the network, it could be seen that the electrical systems maintain a stable behavior that does not exceed its voltage limits by not having distributed generation in its system, However, when distributed generation sources are connected to the grid, this presents variations in the system which exceed their voltage limits. To analyze these behaviors, a research was carried out using the descriptive method that helped us to collect information and then to analyze the data. To evaluate the behavior of the distribution network we used the analytical method that consists of determining the state of all the elements of the network and finally we used a systematic method to model renewable energy sources, for this we propose to develop a model of the electrical distribution system and implement a distributed generation system that is done through a simulation in the OpenDss software taking one of the cases proposed by the IEEE Distribution System Analysis Subcommittee - 123 Nodes Test Feeder of the Institute of Electrical and Electronics Engineers, which will be modeled without implementation of distributed generation and thus be able to observe the normal behavior of this network, therefore a modification will be made in this model in which the implementation of distributed generation in the different load nodes will be performed, Thus obtaining results where it can be seen that the system without distributed generation has losses of 96 kW in its lines, when entering our first case study can be seen how these losses are reduced by 40% of the total losses of the system, a second case study where you can see that the losses are much more minoran becoming 60% less than the total system.